Managing Risk with Insurance and Savings : Experimental Evidence for Male and Female Farm Managers in the Sahel - Delavallade, Clara; Dizon, Felipe; Vargas Hill, Ruth; Petraud, Jean Paul (World Bank Group, Washington, DC, 2015)
Although there is fast-growing policy interest in offering financial products to help rural households manage risk, the literature is still scant as to which products are the most effective. This paper uses a randomized field experiment in Senegal and Burkina Faso to compare male and female farmers who are offered index-based agricultural insurance with those who are offered a variety of savings instruments. The paper finds that female farm managers were less likely to purchase agricultural insurance and more likely to invest in savings for emergencies, even controlling for access to informal insurance and differences in crop choice. It is hypothesized that this finding results from the fact that, although men and women are equally exposed to yield risk, women face additional sources of lifecycle risk -- particularly health risks associated with fertility and childcare -- that men do not. In essence, the basis risk associated with agricultural insurance products is higher for women. Purchasing insurance increased input spending and use more than savings. Those who purchased more insurance realized higher average yields and were better able to manage food insecurity and shocks. This finding suggests that gender differences in demand for financial products can have an impact on productivity, resilience, and welfare.